The Connotation, Problems, and Practice of the Integration and Development of Vocational Education and Private Economy - Liu, Lu (Journal of Theory and Practice of Social Science, 2023)
The integration and development of vocational education and private economy is an important focus and direction for the new model of vocational education. This article first clarifies the connotation and three characteristics of vocational education and private economy: deep integration, interactive development, and coordinated innovation. Then, it discusses the insufficient motivation for private enterprises to participate in vocational education, slow professional updates in vocational colleges, and imperfect linkage mechanism between vocational education and private economy The difficulties and problems in the integration of vocational education and private economy development projects were analyzed, and finally, suggestions were put forward from the aspects of strengthening top‐level design, promoting the cultivation of technical and skilled talents, strengthening the construction of dual teacher training bases, and deepening the integration of industry and education in vocational colleges, in order to provide reference for promoting the integration of vocational education and private economy development.